The impact of absorbing productivity spillover on export ability: evidence from an emerging market - Pham Thi Bich Ngoc; Pham Dinh Long; Huynh Quoc Vu (Cogent Economics & Finance, 2022)
This paper examines spillover effects of foreign direct investment (FDI) through horizontal, backward, and forward linkages, and how these spillovers are driven by the exporting ability for Vietnamese manufacturing enterprises. Those participating in export activity can increase the spillover absorption from FDI through the horizontal and backward linkages although local firms are less likely to take advantage of productivity spillovers during this period. In addition, these exporting firms confront the productivity protection of the FDI firms in the same industries. In contrast, the higher their exportability is, the better their learning from the foreign firms in the same downstream sectors becomes. The findings of this paper provide valuable evidence and implications for policymakers in managing and enhancing export ability for firms in the emerging market.
Keywords: 330; export ability; foreign direct investment; Spillover effects; total factor productivity